Prevention And Control Of Cyber Crimes - Kaur, Dr. Navneet (IJRDO -Journal of Computer Science Engineering, 2016)
Computers and their use is a day-to-day activity of all the students, professionals, teachers, universities, and banks, supermarkets, in the entertainment field, in medical profession and also in higher education. The use of this weapon is spreading vary widely in all parts of our society. As every weapon has two ways of operation, one is good and essential and the other is bad and not essential. Many times, whenever a new weapon is invented, many people use it unknowingly for the wrong purposei . So to aware them and to make the proper use of the power of the newly invented weapon, laws are to be formulated and should be implemented. Cyber crime is a generic term that refers to all criminal activities done using the medium of computers, the Internet, cyber space and the worldwide web. There isn’t really a fixed definition for cyber crime. The Indian Law has not given any definition to the term „cyber crime‟. In fact, the Indian Penal Code does not use the term „cyber crime‟ at any point even after its amendment by the Information Technology (amendment) Act 2008, the Indian Cyber law But “Cyber Security” means protecting information, equipment, devices computer, computer resource, communication device and information stored therein from unauthorized access, use, disclosure, disruption, modification or destruction. The word “cyber law” encompasses all the cases, statutes and constitutional provisions that affect persons and institutions who control the entry to cyber space provide access to cyberspace, create the hardware and software which enable people to access cyberspace or use their own devices to go “online” and enter cyberspace. In simple way we can say that cyber crime is unlawful acts wherein the computer is either a tool or a target or both. Cyber crimes can involve criminal activities that are traditional in nature, such as theft, fraud, forgery, defamation and mischief, all of which are subject to the Indian Penal Code. The abuse of computers has also given